#### Answer

The point-slope form of the equation for this line is:
$$y + 1 = -2(x - 3)$$
The slope-intercept form of the equation for this line is:
$$y = -2x + 5$$

#### Work Step by Step

We use the slope and the point given to write the equation of the line in point-slope form:
$$y - y_{1} = m(x - x_{1}$$
Plug in the information given into this equation:
$$y - (-1) = -2(x - 3)$$
Simplify the equation on the left-hand side:
$$y + 1 = -2(x - 3)$$
Now, we find the y-intercept by plugging in $0$ for $x$ and then solving for $y$:
$$y + 1 = -2(0 - 3)$$
Evaluate parentheses first:
$$y + 1 = -2(-3)$$
Multiply right side of the equation:
$$y + 1 = 6$$
Subtract $1$ from both sides to solve for $y$:
$$y = 5$$
Now that we have the y-intercept, we can plug it into the slope-intercept equation, which is $y = mx + b$, where $m$ is the slope and $b$ is the y-intercept:
$$y = -2x + 5$$